2017
DOI: 10.1097/scs.0000000000003196
|View full text |Cite
|
Sign up to set email alerts
|

Stapler Esophageal Closure During Total Laryngectomy

Abstract: Mechanical esophageal closure with stapler during total laryngectomy has been used by various authors to decrease the surgical time and pharyngocutaneous fistula (PCF) rates. In a few of the studies, surgical site infection (SSI) rates are mentioned and none of the studies emphasize the effect of decreased surgical time on postoperative cardiovascular and cerebrovascular complications. In this study, the authors compared the PCF rates, SSI rates, operation times between 30 mechanical stapler and 40 manual esop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…In most studies, mechanical sutures were associated with a significantly lower fistula rate than manual sutures. 8,12,13,17 For other studies, the results were comparable, 14 or the fistula rate was higher in patients treated with mechanical sutures although there was no significant difference. 15 According to the results of a meta-analysis carried out by Aires et al, the overall incidence of fistula in patients who underwent the mechanical suturing technique was 8.7 per cent, compared to 22.9 per cent in patients with manual sutures.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…In most studies, mechanical sutures were associated with a significantly lower fistula rate than manual sutures. 8,12,13,17 For other studies, the results were comparable, 14 or the fistula rate was higher in patients treated with mechanical sutures although there was no significant difference. 15 According to the results of a meta-analysis carried out by Aires et al, the overall incidence of fistula in patients who underwent the mechanical suturing technique was 8.7 per cent, compared to 22.9 per cent in patients with manual sutures.…”
Section: Discussionmentioning
confidence: 76%
“…All the research indicates that the use of mechanical sutures achieves a reduction in surgical time. 7,8,13,17 Regarding the results of the meta-analysis by Aires et al ., 19 the average difference in surgical time was 80 minutes (95 per cent confidence interval = 23–136 minutes, p < 0.006). Considering the retrospective nature of our study, we cannot provide information about the surgical time reduction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 The closure of pharyngoesophagectomy with stapler takes ∼ 5 minutes, while manual closing takes much longer, and its duration is relative to the experience of the surgeon. According to some authors, 15 19 the stapler reduces the duration of the surgery in ∼ between 45 and 80 minutes. All of the previous studies, excluding the one by Dedivitis et al, 7 despite their lack of homogeneity, reported a benefit in reducing the appearance of PCF in patients who underwent TL with the closure of the pharyngoesophagectomy with a stapler.…”
Section: Discussionmentioning
confidence: 99%